Implementation of Learning Organization in School (Sains Humanika, 2021)
The human resource development aspect is an important and significant element in ensuring a school organization to achieve and realize the vision and goals of the school organization. To ensure that school organizations respond appropriately, responsively and efficiently to all challenges and expectations in the 21st century, school organizations are required to implement transformation and transition into a genuine learning organization in order to survive and maintain their excellence. The current study aims to investigate the level of implementation of learning organization practices in school organization according to teachers' perceptions in Melaka Tengah District, Melaka. This study employed a quantitative research design. Using the instrument, Learning Organisation Practices Profile (LOPP), the study collected data from 500 teachers from thirteen school organization located in Melaka Tengah District, Melaka that is chosen based on cluster and simple random sampling. Statistical Package for Social Science (SPSS) 25 for Windows was used to analyze the Learning Organization practices in the school organization. Based on the analysis of mean scores obtained from the twelve components contained in LOPP, it was found that the level of learning organization practice in the school organizations studied is at a high level. The most practiced components in the school organization studied are organizational climate, information flow and executive practices while the least practiced and need to be given more emphasis are the reward and recognition component, management practices and performance goals and feedback. The findings of this study show the importance of developing human resources by cultivating a culture of learning organization in school organizations.